Profile Understanding Student S-1 PGSD-BI-UT Surabaya in Implementing Practices of Natural Sciences - Iriyani, Dwi; Asnawi, Asnawi; Farisi, M. Imam (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.634, 2017)
The low achievement of elementary school students especially in science subjects. Many components are related to science and one of them is the teacher. Factors sourced from the teacher must receive serious attention such as low knowledge, commitment, performance and educational background of teachers. To improve the knowledge-based society, the Open University Distance Learning Program Unit (UPBJJ) Surabaya in collaboration with the district/city government in East Java opened the S-1 Primary School Teacher Education Program in various disciplinary inputs which became known as S1 PGSD-BI which I then call as a teacher. This study aims to describe the understanding and skills of science students in the implementation of science and the use of science in laboratory UT-UPBJJ Surabaya. The expected result of this research is to improve teachers in performing their duties professionally which in turn will lead to the improvement of science process skills and student learning outcomes. The method used in this research a quasi-experiment. The results of the first stage of the study were obtained based on questionnaire and observation of teachers in carrying out the science practice is as follows: the competence of mastering the science laboratory material showed (79.2%) the teachers have not been able to optimally practice the science, especially on the topic, Wave, and Optics. Similarly, on the topic of Living and Environment, especially on the subject of "Detergent Effect on Germination" (62.5%) of Primary School Teachers is less well controlled. However (87.5%) teachers can master fairly well on Topics of Life, Food, Electrical, and Magnetism. Similarly, the competence of teachers' science process skills (63.8%) in observing, classifying, inference, application and communicating well enough and (75%) teachers lacking in predicting and planning experiments. From the questionnaire, it was identified various things that caused the teachers to feel reluctant to carry out the science lab in the classroom/laboratory, among others: the limited time of practicum implementation, the absence of labor that can help the implementation of the lab besides the lack of equipment and practicum materials, the low understanding of the teacher on the concept and use of tools practice tools and lack of teacher intensity in the laboratory training